GOD AND COSMOS AS REALITY: An Inquiry to the Interconnection among Islamic Philosophical Doctrine - Zarkasyi, Hamid Fahmy; Arroisi, Jarman; Taqiyuddin, Muhammad; Salim, Mohammad Syamâ€™un (Jurnal THEOLOGIA, 2019)
In the Islamic intellectual tradition,Â BeingÂ (wujÅ«d) is not limited to physical things. God is also understood as Being; indeed, He is the Absolute Being itself; which of Him, manifests all metaphysical and physical realities. This physical nature is one of the realities caused by God; as well as the metaphysical reality of 'natural law' called 'sunnatullÄh' in Islam. It is necessary to know how the power of God can connect to this universe. The question presupposes cosmological research, which needs to involve the study of God and His attributes as well. Methodologically, the verification of Islamic philosophical ideas among Muslim philosophers to Sufis, involves the development of the key concept from tafsÄ«r and ta'wÄ«l among the Quranic verses (Äyat) that discuss God's relationship with Nature itself; from this framework, the relationship between the two can be explained. This article, offers a study of the views of Muslim thinkers: from philosophers to Sufis, about the relationship; which specifically highlights that God and Nature are part of the concept of 'reality' in the Islamic view. The study concludes several important things, especially that God is the Absolute Being; which from Him, another reality as the sign (Äyat) of His Existence created. His sunnatullÄh again manifests in Godâ€™s creatures that undergo being devastated and recreated.